How do you solve 43= - 5( y + 11) + 7y43=5(y+11)+7y?

1 Answer
Sep 21, 2017

y=49y=49

Explanation:

First we switch sides from
43=-5(y+11)+7y43=5(y+11)+7y to -5(y+11)+7y=5(y+11)+7y=.
We will remove the 7y7y and the 43=43= and focus on the rest.
We will distribute parentheses/brackets using:
a(b+c)=ab+aca(b+c)=ab+ac.

aa would be -55, bb would be yy and cc would be 1111 in this case.

Using a(b+c)=ab+aca(b+c)=ab+ac, we know that -5*y-5*115y511. Multiply -5*y=-5y5y=5y and 5*11=55511=55. Therefore the equation would be (with the 7y7y) -5y-55+7y5y55+7y.

Next, we group like terms: -5y+7y-555y+7y55, and then add -5y+7y=2y5y+7y=2y.
The whole equation will then be 2y-55=432y55=43. Add 5555 to both sides:

2y-55color(blue)+color(blue)55=43color(blue)+color(blue)552y55+55=43+55 and simplify it to be 2y=982y=98.
Divide both sides by 22 and you get y=49y=49.